Art and Analysis - Ballard, Edward G. author. aut Link
XVI, 219 p. 1 illus.
Keywords: Aesthetics, fledgling of the philosophic brood, is the most suspect of that family. It is suspected of all the philosophical sins: vagueness, disorder, dogmatism, emotionalism, reductionism, compartmentalization. Sometimes its youth is thought to be a sufficient excuse for these divagations. Sometimes the very nature of its content, involving the waywardness of genius, the remoteness of feeling from intellect, the surd of inspiration in even the mildest appreciation, are believed to condemn aes thetics irrevocably to the underside of the civilized man's domain. Some philosophers have gloried in this apparently mystical and a-rational quality and have seen in it the very nature of the beautiful; others have come to regard it, rather, as evidence of the unskillfulness of our minds and have turned away from aesthetic problems to the task of sharpening the aesthetician's language and logic. The laughter of the gods is not difficult to discern through the poetry of the more mystical aesthetician or through the prose of the analysts. Meanwhile the manifold complexities and problems of aesthetic experience invite our understanding. For aesthetic experience is a present fact of human life and may, perhaps, be understood by men. Such, at least, will be the present assumption. This is the reason why the title of this book mentions art together with analysis; for if art is intelligible, the work of art and the experience of it may be analyzed into its functional parts.